PENYULUHAN HUKUM PERUSAHAAN PERSEROAN TERBATAS PERSEORANGAN DI DESA SIGERONGAN KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - I Gusti Agung Wisudawan; Ari Rahmad Hakim Budiawan Firdaus; Diman Ade Mulada; Lalu Achmad Fathoni; I Nyoman Ari Widiantara (LPPM Institut Pendidikan Nusantara Global, 2026)
This paper focuses on increasing awareness and empowerment for MSMEs in Sigerongan Village regarding the importance of establishing a Sole Proprietorship Limited Liability Company consisting of an understanding of the concept and legal basis of a Sole Proprietorship Limited Liability Company, the requirements and procedures for establishment, legal entity status, the structure of Sole Proprietorship Limited Liability Company organs, the legal responsibilities of a Sole Proprietorship Limited Liability Company, dissolution and liquidation, good Governance of a Sole Proprietorship Limited Liability Company and supervision. The type of research used is Normative-Empirical. Types and Sources of Legal Materials/Data used consist of Primary Data, namely interviews and discussions with informants (Sigerongan Village officials) and Respondents, namely MSME Actors in Sigerongan Village, and Secondary Data consisting of Legal Materials, namely Primary Legal Materials, namely Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation and Government Regulation Number 8 of 2021 concerning Authorized Capital of Companies and Registration of Establishment, Amendments, and Dissolution of Companies that Meet the Criteria for Micro and Small Enterprises. Secondary Legal Materials, namely literature and scientific articles related to the problems raised in this study and Tertiary Legal Materials, namely the Big Indonesian Dictionary and Encyclopedia. Legal Material/Data Collection Techniques used in this study are Interviews and Documentation Studies with Legal Material/Data Analysis, namely Qualitative Descriptive Analysis with deductive conclusions. The result of this legal outreach activity is that MSME actors in Sigerongan Village have increased their awareness and understanding of the legal aspects of individual limited liability companies.